2023
DOI: 10.1177/0308518x231209982
|View full text |Cite
|
Sign up to set email alerts
|

Planning deregulation as solution to the housing crisis: The affordability, amenity and adequacy of Permitted Development in London

Ian Chng,
Jonathan Reades,
Phil Hubbard

Abstract: Since 2013, Permitted Development Rights (PDR) in England have allowed commercial-to-residential conversions in locations once deemed suitable only for non-residential land-use. This deregulation of planning control has been justified as a way of encouraging more home-building in areas experiencing ‘housing crisis’, but its overall consequences remain unclear. This paper hence compiles quantitative evidence on a city-wide scale on the price, size, build and location of these conversions in London 2013–2021. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Hence, while many sources have suggested Permitted Development Rights are a major source of small homes, Figure 4 suggests most small homes either predate the Prior Approval process introduced in 2013 or were granted formal planning permission by the local authority in question (noting some of the divergence visible in 2020 and 2021 may be because units were not yet recorded as completed in the London Development Database despite having been issued an EPC). Related examination of the London Planning Database suggests only around 15% of units in major PDR conversions of more than 10 units are below the NDSS (see Chng et al, forthcoming), a figure lower than suggested in some other, more narrowly-focussed, studies of permitted development (Clifford and Ferm, 2021).
Figure 4.Newly-built homes granted an EPC, 2010–21, comparing those with planning permission and those completed via PDR.
…”
Section: Small Domestic Properties In London 2010–21mentioning
confidence: 76%
“…Hence, while many sources have suggested Permitted Development Rights are a major source of small homes, Figure 4 suggests most small homes either predate the Prior Approval process introduced in 2013 or were granted formal planning permission by the local authority in question (noting some of the divergence visible in 2020 and 2021 may be because units were not yet recorded as completed in the London Development Database despite having been issued an EPC). Related examination of the London Planning Database suggests only around 15% of units in major PDR conversions of more than 10 units are below the NDSS (see Chng et al, forthcoming), a figure lower than suggested in some other, more narrowly-focussed, studies of permitted development (Clifford and Ferm, 2021).
Figure 4.Newly-built homes granted an EPC, 2010–21, comparing those with planning permission and those completed via PDR.
…”
Section: Small Domestic Properties In London 2010–21mentioning
confidence: 76%